Hybrid Strategy based Timetable Rescheduling for High-Speed Railways under Disturbances - Shang, Jingfan; Zhou, Min; Duan, Qingpei; Li, Ye; Dong, Hairong (Chinese Automation Congress (Online), 2021)
High-speed railways are occasionally subject to emergencies such as extreme weather, device faults or foreign matter intrusion, and these circumstances will lead to train delays when trains fail to run as the original plan. Rescheduling strategies are an important part of train dispatching in dealing with train delays. This paper proposes the hybrid strategy to solve the timetable rescheduling problem for high-speed railways under disturbances. A mixed-integer linear programming model is built with consideration of train retiming, reordering, limiting overtaking times and increasing unplanned dwellings. To minimize the total delay time, a genetic algorithm is used to optimize the objective function. The part of Beijing-Shanghai high-speed railway line is used to verify the effectiveness of the proposed hybrid strategy. The simulation results indicate that, under different delay scenarios, the rescheduling strategy proposed in this paper reduces the total delay time by more than 25% and 12% respectively when it is compared with the FCFS (First Come First Served) rescheduling and the strategy of limited overtaking times and unplanned dwellings. It limits the trains overtaking times and ensures fairness in the operation between different classes of trains.